Spin-State-Controlled Photodissociation of Iron(III) Azide to an Iron(V) Nitride Complex - Andris, Erik; Navrátil, Rafael; Jašík, Juraj; Sabenya, Gerard; Costas, Miquel; Srnec, Martin; Roithová, Jana (Angewandte Chemie (International ed. in English), 2017)
The generation of iron(V) nitride complexes, which are targets of biomimetic chemistry, is reported. Temperature-dependent ion spectroscopy shows that this reaction is governed by the spin-state population of their iron(III) azide precursors and can be tuned by temperature. The complex [(MePy2 TACN)Fe(N3 )]2+ (MePy2 TACN=N-methyl-N,N-bis(2-picolyl)-1,4,7-triazacyclononane) exists as a mixture of sextet and doublet spin states at 300 K, whereas only the doublet state is populated at 3 K. Photofragmentation of the sextet state complex leads to the reduction of the iron center. The doublet state complex photodissociates to the desired iron(V) nitride complex. To generalize these findings, we show results for complexes with cyclam-based ligands.
Keywords: iron(V) nitride; photooxidation; ion spectroscopy; spin crossover; photodissociation